CULTURAL ENTREPRENEURSHIP AND THE DIGITAL ECONOMY: EMERGING BUSINESS MODELS IN PERFORMING ARTS - Arasu, R; Dutta, Mili; Sharma, Sonali; Jain, Preeti; Kumar, Vinod; Singh, Pooja; Kumar, Brijesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This has been greatly influenced by high development rate of the digital economy thus leading to new forms of cultural entrepreneurship and new business models in the performing art industry. This paper examines how digital technologies can contribute to the business model development of performing arts, in its sustainability, interactions with the audience, and the creation of value. Based on the theories of cultural entrepreneurship, digital entrepreneurship and the platform economy, the paper presents a conceptual model, which combines the cultural creativity with the technological adoption and business model innovation. The research method is a mixed-method study, which includes quantitative survey analysis and qualitative knowledge about conduct and practice of performing arts using interviews and case studies of practitioners and organizations in the performing arts sector. The results indicate that the adoption of digital technologies is a significant mediator of the ability to facilitate new types of business processes like hybrid performances, subscription-based platforms, crowdfunding, and blockchain-enabled monetization. The models increase the world coverage, better revenue diversification, and interactive audience. The paper also displays the moderating nature of the audience participation in enhancing the relationship between innovation and sustainability. Digital and hybrid models have been found to be better in scalability, accessibility, and long-term viability compared to traditional models, but issues of platform dependency, digital inequality, and intellectual property issues still remain. The results provide an insight into the need to strategically combine digital means and approaches to art to achieve economic and cultural sustainability. The research is an addition to the literature since it provides an extensive framework of the understanding of the cultural interaction of entrepreneurship and digital economy in the performing arts. It offers a real-life lesson to artists, cultural organizations, and policymakers who can seek to negotiate and make ends meet creative enterprises in a more digitalized world.